OPTIMAL DIRECTIONS OF the cable television DIGITAL networks development - V. I. Kirillov; K. A. Kauryha (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The main tendencies of the development of the city-wide networks of cable television are allocated; the model of the integration of head stations of cable television into the existing fiber-optical network of the city of Gomel is given for example.